1985
DOI: 10.1111/j.1432-1033.1985.tb09295.x
|View full text |Cite
|
Sign up to set email alerts
|

Structures of the major carbohydrates of natural human interleukin‐2

Abstract: Purified human interleukin-2 secreted by peripheral blood lymphocytes from healthy donors was found to exist in several forms. These forms were (partially) resolved by reversed-phase high-performance liquid chromatography and sodium dodecyl sulfate/polyacrylamide gel electrophoresis. Two major polypeptide species (interleukin-2 N, and N2, 16.5 kDa) were shown to be glycosylated on the basis of [3H]galactose/[3H]glu~o~amine incorporation and determination of amino sugars after acid hydrolysis. A third component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…This result suggests that, even though the N-terminal region included the glycosylation site Ser4, these N-terminal domains were not completely 0-glycosylated. The amino terminal domain of TNF-a is probably a poor substrate for a l -0 GalNAc transferase in the lumen of the Golgi apparatus, as in the case of interleukin-2 [27]. Thus, slight post-translational O-glycosylation of the peptides may only have a slight effect on the protection of the peptides from additional proteolytic degradation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result suggests that, even though the N-terminal region included the glycosylation site Ser4, these N-terminal domains were not completely 0-glycosylated. The amino terminal domain of TNF-a is probably a poor substrate for a l -0 GalNAc transferase in the lumen of the Golgi apparatus, as in the case of interleukin-2 [27]. Thus, slight post-translational O-glycosylation of the peptides may only have a slight effect on the protection of the peptides from additional proteolytic degradation.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the N-glycosylation site, the amino acid sequence motif of the 0-glycosylation site has not been identified, but the region including the 0-glycosylation site often contains a hydroxylamino acid cluster. In the case of TNF-a, the amino acid residues near the 0-glycosylation site (NH,-V-R-S-S-S-R-T-P-) also contained a hydroxylamino acid cluster, as for interleukin-2 [27].…”
Section: Discussionmentioning
confidence: 99%
“…A potential O-glycosylation site is present at the first Thr residue of the IL2 moiety fused to the C-terminal part of the IgG heavy chain corresponding to amino acid position 3 (in the sequence APTSSSTKKT of the human IL2 molecule) (Fig. 1) that has been shown to be occupied with O-linked carbohydrate in the wild-type human IL-2 expressed from BHK-21 cells (Conradt et al, 1985;1989).…”
Section: N-glycosylation Analysis Of the Recombinant Human Igg-il2 Fumentioning
confidence: 98%
“…It has also been shown that atRA can alter the glycosylation pattern of various proteins (59 -61) and glycosylation of proteins is known to affect, for instance, the protein stability (62,63). IL-2 has a single O-linked carbohydrate chain at position Thr-3 in the protein (64), but inhibiting O-glycosylation using benzyl 2-acetamido-2-deoxy-␣-D-galactopyranoside did not affect the atRAmediated induced secretion of IL-2 (data not shown), indicating that this modification is not important for the effects we observe.…”
Section: Discussionmentioning
confidence: 99%